Clinical and pathological responses of West African Dwarf goats (Fouta Djallon) infected with Nigerian strains of Wesselsbron virus - Baba, S.S.; Fagbami, A.H.; Olaleye, O.D. (1988)
The pathogenicity of Wesselsbron virus was investigated in West African Dwarf goats infected subcutaneously with the Nigerian strain of the virus. All infected goats were susceptible to infection. Two of the infected animals developed an acute disease with death occurring within 5-8 days post inoculation (P.I.). The others had a relatively protracted disease lasting between 18-20 days following the incubation period. The disease was characterized by profuse diarrhoea, dehydration, weight loss and 100% mortality. The associated haematological changes include relative polycythaemia, which was associated with dehydration in infected animals. There was leucopaenia characterized by lymphocytopoenia. The pathological changes include widespread hepatic necrosis and haemorrhage coupled with widespread congestion and dilation of meningeal and cerebral blood vessels.